The ion-trap facility SHIPTRAP: status and perspectives - Block, Michael; Herfurth, Frank; Kluge, Heinz-Jürgen (The European physical journal. A, Hadrons and nuclei, 2005)
The Penning-trap mass spectrometer at the ion trap facility SHIPTRAP is in the final stage of commissioning. First on-line mass measurements of neutron-deficient radionuclides in the rare-earth region around A = 147 were performed in July 2004. Systematic investigations in order to determine systematic errors are ongoing. Further improvements of the efficiency of the system are in preparation, e.g. improved detection schemes and further optimization of the stopping cell. SHIPTRAP will then address exotic nuclides produced in fusion-evaporation reactions at the velocity filter SHIP. This production technique will give access to nuclei not available at ISOL facilities, especially in the transuranium region.